Numerical assessment of mixing of humid air streams in three-way junctions and impact on volume condensation. (25th January 2022) - Galindo, José; Gil, Antonio; Navarro, Roberto; García-Olivas, Guillermo
Abstract: Flow mixing at three-way junctions is widely studied due to its usage in countless applications. Particularly, in air conditioning and internal combustion engines, the mixing of humid air streams can lead to volume condensation, provided that any local temperature achieves dew conditions. This work investigates and quantifies the correlation between mixing intensity and generated condensation. A method to define mixing indexes is developed, comparing its performance against literature references that employ temperature or passive scalar to evaluate mixing. A numerical campaign of 128 Reynolds-Averaged Navier Stokes three-dimensional (3D) simulations is designed to explore different junction operating conditions. A validated condensation submodel embedded in the 3D model enables the quantification of condensation at the junction outlet, which also can be estimated by means of a 0D model that provides the psychrometric state of a homogeneous mixture between the inlet streams. A strong linear correlation is found between condensation and the product of mixing indexes and 0D condensation mass flow rate, since the latter carries the psychrometric information of the working point. This connection allows to find junction design guidelines to reduce mixing and therefore condensation. Additional simulations confirm that removing junction valves, reducing mixing length, increasing the branch duct diameter and aligning the branch leg with the outlet duct significantly decrease condensation. In the framework of low pressure exhaust gas recirculation (EGR), this condensation damages the compressor wheel. If junctions are designed as suggested, the current constraints over EGR rates to limit condensation can be removed, which will result in internal combustion engines with lower emissions and better fuel consumption. Highlights: A new definition of mixing index is developed by calculating the unmixed area. Flow mixing and condensation at T-junctions is assessed using 0D and 3D models. Condensation is strongly correlated with psychometric conditions and mixing. Mixing is reduced by decreasing length and momentum ratio and relocating valves. Guidelines to design junctions with reduced volume condensation are provided.